The Wess-Zumino-Witten term in non-commutative two-dimensional fermion models - Moreno, Enrique Francisco (2000)
We study the effective action associated to the Dirac operator in two dimensional non-commutative Field Theory. Starting from the axial anomaly, we compute the determinant of the Dirac operator and we find that even in the U(1) theory, a Wess-Zumino-Witten like term arises.